Effect of Aerogel on Thermal Protective Performance of Firefighter Clothing (Journal of Fiber Bioengineering and Informatics, 2013)
The aim of this study is to evaluate the effect of aerogel on Thermal Protective Performance (TPP) offire fighter clothing. Specimens were treated by 5 wt% aerogel dispersed in acetone to obtain variousfiadd-on of aerogel and their TPP were evaluated by flame heat transmission test according to ISO 9151.The thermal degradation behavior, flame retardancy and water vapor permeability of aerogel treatedspecimens were also examined. Finally, the comparison of the burn injuries predicted by instrumentedmanikin testing of aerogel treated fire fighter clothing and existing fire fighter clothing were performed.The result showed that aerogel treated fire fighter clothing exhibited higher TPP than the existingfirefighter clothing. This suggests that there application of aerogel in fire fighter clothing may be possible.
Keywords: Aerogel; Thermal Protective Performance; Firefighter Clothing; Instrumented Manikin Test